Increasing Student Entrepreneurship Interest Through Entrepreneurship Skills Training Program in Higher Education in Banten - Nely Hartika (MultiTech Publisher, 2023)
Entrepreneurship is a crucial aspect in driving economic growth and creating new job opportunities in Indonesia. Students hold significant potential as future entrepreneurs; however, their interest in entrepreneurship remains low. Entrepreneurship training programs in universities in Banten aim to enhance students' entrepreneurial interest. This research evaluates the effectiveness of these programs and identifies factors influencing students' entrepreneurial interest. The results indicate that effective training programs can significantly increase students' entrepreneurial interest, with a notable shift from low to high interest levels. Factors such as positive attitudes, motivation, family and peer support, entrepreneurship education, and university support play pivotal roles in shaping entrepreneurial interest. The implications of this research encompass program expansion, a holistic approach, and the crucial role of universities in fostering entrepreneurial interest. This study is relevant in the context of Banten, which faces low entrepreneurial interest, and can serve as a guideline for efforts to boost entrepreneurial interest and economic growth in the region.